Glomangioma of the knee with no response to sclerotherapy - Mahboubeh Rahmani, MD; Mark D. Iafrati, MD; Stephen P. Naber, MD, PhD (Elsevier, 2017)
Glomus tumors are rare usually benign tumors derived from a neuromyoarterial apparatus called the glomus body, which is great in number in the digits and helps to control body temperature. Glomus tumors are usually subungual; however, they have been reported in unusual locations such as viscera and other parts of the extremities. Glomangioma is a variant of glomus tumor and the two entities have minimal histologic differences.We report a case of glomangioma of the knee, which was previously diagnosed as hemangioma approximately 15 years ago, and was treated multiple times with sclerotherapy. The tumor recurred each time after the sclerotherapy and started to slowly grow. Finally it was surgically excised and the diagnosis was made based on histopathology.This case demonstrates that glomus tumors should be considered in the differential diagnosis of vascular lesions which recur after sclerotherapy even in locations not typically associated with glomus tumors such as the knee. This possibility supports the benefit of surgical excision in refractory vascular lesions to support both diagnosis and more definitive treatment.